Pengaruh Motivasi, Minat, dan Intensitas Belajar Terhadap Hasil Belajar Siswa Pada Pengantar Akuntansi dan Keuangan - verol wahyu diny putra; Agung Listiadi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
Student learning outcomes at this time are the effect of multiple factors which can be internal and external. The purpose of this study is to analyze the effects of variables (learning motivation, interest in learning, and learning intensity) in class XI students of Introduction to Accounting and Finance at SMK Negeri 10 Surabaya. The type of this research is quantitative. The population in this study were 144 students of class XI SMK Negeri 10 Surabaya and were sampled by means of Non Probability Sampling or sampling techniques that did not provide equal opportunities / opportunities for each element or member of the population to be selected as samples and the sampling technique used was used was purposive sampling with certain criteria, namely students of class XI Accounting. After conducting the research, the conclusions are (1) The results of this study indicate a significant value of less than 5% (0.007 <0.05) that the learning motivation of students has a positive and significant effect on learning outcomes introducing accounting and finance (2). This also shows a significance value of less than 5% (0.000 <0.05) which means that the learning motivation of students has a positive and significant effect on learning outcomes introducing accounting and finance (3) in research research shows the significance value also shows less than 5 % (0.008 <0.05) that the learning intensity of students has a positive and significant effect on learning outcomes introducing accounting and finance (4) For the results of hypothesis testing, the F test shows a significance value of less than 0.05, namely 0.000. The results of this study indicate that the variables of learning motivation (X1), Learning Interest (X2), and Learning Intensity (X3) simultaneously have a positive effect on learning outcomes introducing accounting and finance (Y) in class XI students of SMKN 10 Surabaya.